Autocrine signaling of type 1 interferons in successful anticancer chemotherapy - Vacchelli, Erika (Oncoimmunology, 2015)
Anthracycline-based chemotherapies are particularly effective if they succeed in reinstating immunosurveillance by the induction of immunogenic cell death (ICD) in the tumor. Recently, we discovered that ICD is coupled to the induction of type 1 interferons (IFNs-I) that act in an autocrine fashion on cancer cells, thereby increasing their immunogenic potential.